Pembelajaran Bahasa Inggris (Together We Learn, Together We Grow) untuk Anak-Anak Marind-Papua dan Putus Sekolah di Bivak Pintar Wasur Kampung Kabupaten Merauke - Margaretha F Narahawarin; Marnina Marnina; Angla F Sauhenda; Marni Bawawa (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The implemetation of this service activity aims to facilitate and assist Marind Papuan children and Marind dropout children to learn the use of English in a fun, interactive and appropriate way for children, train Marind-Papuan children and dropouts to be able to write, read as well as develop their abilities to develop and advance so that they can speak English by using the Bivak Pintar (Pondok) facility which will be used for this activity. This service was carried out at theWasur Kampung, Merauke Distrik. The duration is 7a week through the application of theory and practice with a total number of participants of 35 people. This service is carried out in the form of workshops, training and mentoring., while the methods used in this activity are: (1) provide a handbook that is used during activities that contain material to be studied; (2) providing material, namely providing basic material according to their abilities so that it can help children grow their English learning skills until they understand; (3) provide exercises by explaining and explaining the material after that make questions about the vocabulary that has been explained. The expected results of this dedication are: (1) increased knowledge and understanding of indigenous Papuan children who have dropped out of school about the importance of learning English, and how it can be used in the world of work; (2) improved English writing and reading skills for indigenous Papuan children dropping out of school;